2010
DOI: 10.2176/nmc.50.482
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Chronic Subdural Hematoma Infected by Escherichia Coli -Case Report-

Abstract: A 6-month-old boy presented with a rare case of infected subdural hemorrhage manifesting as sustained fever and focal seizure. The boy had been well without contributory medical history. Physical examination found no neurological impairment with intact superficial appearance and soft fontanels. The parents denied recent head trauma or shaking injury. Blood examination was normal except for white blood cell count of 19200/ml and C-reactive protein level of 6.7 mg/dl. Bacterial culture of nasal swab, urine, stoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“… 20 The limited understanding of E. coli infection is apparent in bacterial meningitis in infants where the predisposing factors were not identified in 70% of patients. 21 In our case, no extracranial infective focus was identified.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“… 20 The limited understanding of E. coli infection is apparent in bacterial meningitis in infants where the predisposing factors were not identified in 70% of patients. 21 In our case, no extracranial infective focus was identified.…”
Section: Discussionmentioning
confidence: 50%
“… 13 14 28 Burr hole drainage alone has been shown to be sufficient for the complete drainage of subdural empyema. 13 21 However, some found that the success rate with craniotomy was superior over burr holes and associated with a lower mortality rate. 8 17 Furthermore, in one study burr hole evacuation of pus resulted in a 40% recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of infected subdural hematoma is quite low, and only 27 cases have been reported in the literature (table 1 ) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Although subdural empyema occurs mainly due to the spread of infectious focus near the cranium, infected subdural hematoma most likely occurs through a hematogenous infection to a preceding chronic subdural hematoma [ 14 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A preexisting subdural hematoma may transform to an infected subdural hematoma mainly through hematogenous infection. According to previous reports, the phlogogenic fungus of an infected subdural hematoma widely varies, including Escherichia coli , Klebsiella , Salmonella and Methicillin-resistant Staphylococcus aureus (MRSA) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. In this report, we present an adult case that developed chronic subdural hematoma infected by Propionibacterium acnes .…”
Section: Introductionmentioning
confidence: 99%
“…Из осложнений, требующих наблюдения нейрохирурга, наиболее важными являются гидроцефалия и развитие хронических субдуральных гематом. Нейроинфекция часто является причиной развития хронических субдуральных гематом [3,8,9,11], наиболее характерной в раннем детском возрасте [1]. В некоторых литературных источниках сообщается о «субдуральном выпоте», обнаруживаемом в 25-50% неонатальных менингитов, которые часто встречаются при инфекционном поражении, вызванном гемофильной палочкой [5].…”
unclassified